Block copolymer derived uniform mesopores enable ultrafast electron and ion transport at high mass loadings - Tianyu Liu (Nature Portfolio, 2019)
High mass loading and fast charge transport are two crucial but often mutually exclusive characteristics of pseudocapacitors. Here, the authors address this challenge by making use of block copolymer phase separation in the synthesis of porous carbon fibres as carbon supports for pseudocapacitors.